Avaliação de novas arquiteturas de carbono para o desenvolvimento de sensores eletroquímicos para a determinação de espécies de interesse em diferentes matrizes de amostras - Silva, Tiago Almeida (Universidade Federal de São Carlos, 2019)
In this doctorate work the efforts were expended in the electrochemical study and electroanalytical application of electrochemical sensors based on two carbonaceous structures: diamond-like carbon (DLC) and carbon black (CB). In the first case, porous DLC films were synthesized over a VACNT (Vertically Aligned Carbon Nanotubes) substrate. The idea of this proposed strategy was to develop an electrodic material combining the conductive properties of carbon nanotubes and the physical and chemical advantages of DLC, eliminating the necessity of use DLC doping procedures and with the generation of a totally carbon, porous and high surface area material. The electrochemical and electroanalytical performance of the porous DLC:VACNT was evaluated towards the determination of analytes of biological (paracetamol, dopamine and epinephrine), pharmaceutical (paracetamol, codeine and caffeine) and dermatologic (hydroquinone) interest by square-wave voltammetry or flow injection analysis with amperometric detection. In the second part of the work, it was focused on the development of modified electrodes based on CB. In this sense, it was evaluated its use as a modifier of glassy carbon electrodes in a individual or combined form with other nanomaterials, namely, ionic liquids and metallic nanoparticles. The proposed modified sensors were applied in the determination of compound of pharmaceutical, food and environmental interests.
Evaluation of novel carbon architectures for the development of electrochemical sensors for the determination of species of interest in different matrice samples
Keywords: Carbono tipo-diamante; Negro de fumo; Sensores; Eletroanalítica; Diamond-like carbon; Carbon black; Sensors; Electroanalytical; CIENCIAS EXATAS E DA TERRA::QUIMICA